UNQUALIFIED OPINION AND LEVEL OF CORRUPTION: THE TRIANGULATION APPROACH - Ronald Tehupuring (Badan Pemeriksa Keuangan Republik Indonesia, 2018)
Corruption cases that occur in almost all provinces throughout Indonesia potentially bring financial harm to the government, drawing public attention in the last few years. A large number of provinces where such cases occur have received Unqualified Opinion. As a result there is a discrepancy between the public's perception and the findings of the BPK, Indonesia's supreme audit institution. The public is assured that government institutions or agencies that have received unqualified opinion are free from potential corruption. On the other hand, there are still potential corruption found that can cause financial harm to the state. Meanwhile, the government (BPK) has not conducted any audit on the financial reports to detect corruption. This inconsistency between public perception and the perception of the government, in this case the BPK, is referred to as an expectation gap. This study aims to prove that an unqualified opinion does not relate to level of corruption. The research method uses a combination of qualitative and quantitative/triangulation approach (mixed method). The study collects samples from 31 provinces throughout Indonesia. The result of this study indicates that an unqualified opinion represents the good governance of an organization. However, such opinion does not necessarily guarantee that the institution is free from potential corruption. The reason is that a BPK audit is not designed to detect corruption, but rather to determine the fairness of information presented in financial reports. Result of quantitative testing conducted during the study also confirms the result of the qualitative testing, and thus it can be affirmed that an unqualified opinion does not significantly relate to corruption level.